Keutamaan Ilmu dan Menuntut Ilmu Menurut Perspektif Hadits dalam Masyarakat 5.0 - Fahad Fahuzi; Ilzam Hubby Dzikrillah Alfani (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study is to discuss the virtues of knowledge and studying according to the hadith perspective in society 5.0. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith takhrij, while the material object is the hadith of Ibn Majah No. 219. The results and discussion of this study indicate that the status of the hadith hasan li ghairihi quality that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Ibn Majah No. 219 is relevant to be used as a basis for studying for the Muslim generation in society 5.0 in the country.